Pengaruh Ekstrak Metanol, Fraksi N-Heksana dan Fraksi Metanol Biji Pepaya (Carica papaya L.) terhadap Motilitas Spermatozoa Tikus (Effect of the Methanol Extract, Hexane Fraction and Methanol Fraction of Papaya Seeds (Carica papaya L.) on Rat Spermato - Novi Prasetyaningrum; Siti Muslichah; Moch Amrun Hidayat (Pustaka Kesehatan, 2015)
Lack of contraceptive choices which meet the requirements is one of the contributing factors to less participation of man in contraceptive use. This research aimed to study the effectiveness of papaya seeds on rat spermatozoa motility. The rats were separated into 4 groups: negative control group (CMC-Na 1%), methanol extract of papaya seeds (100 mg/kg BW) treatment group, n-hexane fraction of papaya seeds (100 mg/kg BW) treatment group, and methanol fraction of papaya seeds (100 mg/kg BW) treatment group. Each treatment group consisted of 5 rats. Each group was administrated orally for 20 days. On 21st day, the rats were sacrified, the spermaatozoa were and were observed on their motility. The data then was anallyzed using Anova followed with LSD. The sperms which moved progressively in negative control, methanol extract, n-hexane fraction and methanol fraction were 67.6%, 29.8%, 38% and 10.6% respectively the methanol fraction of papaya seeds is more potent in reducing sperm motility. Keywords: antifertility, papaya seeds, spermatozoa motility